Rodents/Shrews and their Ectoparasites are not Associated with the Enzootic Maintenance and Transmission of Coxiella burnetii to Livestock and Humans in Puducherry, India - Prathibha A Indhu; V Bhanu Rekha; R Hariharan; V J Ajay Kumar; S Lakshmy; Anand Kasirajan; Thirumurthy Madhavan; D Panneer (Zoonoses, 2024)
“Q fever,” which is caused by Coxiella burnetii , is endemic in India. In addition to livestock, rodents have also been reported to be associated with enzootic maintenance, favoring pathogen transmission. Currently, however, no data are available on the role of rodents in “Q fever” transmission in India. A cross-sectional study was undertaken in 39 Puducherry villages to screen Coxiella burnetii in synanthropic rodents (rats and shrews) and their ectoparasites (ticks, mites, and fleas) by real-time and conventional PCR protocols targeting the pathogen specific IS 1111 and com 1 genes. One hundred forty animals were trapped (107 shrews and 33 rats). The ticks, mites, and fleas infesting the rodents were identified as Rhipicephalus sanguineus , Leptotrombidium deliense and Schoengastiella spp., and Xenopsylla cheopis , respectively. PCR screening of the DNA extracted from the rodent/shrew blood samples and their ectoparasites tested negative for C. burnetii. Synanthropic rodents, such as rodents/shrews and their ectoparasites do not have a pivotal part in the enzootic maintenance and spread of Q fever to humans and livestock in Puducherry.